Hercules Powder Company exhibition display (circa 1950s) - Hercules Incorporated (1950)
General view of the Hercules Powder Company display at an industrial trade show held in Chicago, Illinois showcasing recent company research in rosin and cellulose chemistry. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Advertising, Industrial; Advertising; Chemical industry; Corporations; Hercules Incorporated; Trade shows; Cellulose industry